PENGARUH MOTIVASI, KOMPENSASI DAN BEBAN KERJA TERHADAP KINERJA KARYAWAN PADA PT. BERKAT KARUNIA PHALA DURI, KAB. BENGKALIS - -, Marta Gusliana - (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2023)
This study aims to determine the effect of motivation, compensation and workload on the performance of employees of PT. Berkat Kurnia Phala Duri, Regency. Bengkalis. The population in this study are employees who work in the field at PT. Berkat Kurnia Phala Duri, Regency. Bengkalis as many as 58 people. The type of data used in this research is quantitative data. with data sources used primary and secondary. Primary data is data collected through questionnaires and observations as instruments to prove research results, and secondary data is results obtained from books, journals and the internet. Sampling using saturated sampling technique method, namely taking a population of all employees working in the field as research samples. The data analysis used is descriptive analysis, with a quantitative analysis tool, namely multiple linear regression. Based on the results of the t test it was found that the variables of motivation, compensation and workload had a positive and partially significant effect on employee performance. The results of the f test also show that the variables of motivation, compensation and workload have a positive and significant simultaneous effect on employee performance. Keywords: Motivation, Compensation, Workload and Employee Performance